Child immune response and the role of nutrition - Ariyanto Harsono (Paediatrica Indonesiana, 2005)
The immune function is designed to defendthe body in a safe and efficient way againsta variety of dangerous materials includingtoxins and infectious organisms. Mechanical andbiological barriers prevent the penetration ofexogenous material into the body. Only after thesebarriers have been breached and cells have beendirectly attacked does the immune system come intoplay. By a variety of mechanisms, certain immunecells can directly phagocytose and destroy manypathogens. They require the close cooperation ofsomatic cells, which both alert the immune systemthrough alarm signals and later participate in theeffector phase. This first alarm signal can be groupedtogether as â€œstress signalsâ€, known as the innateimmune response.